Mycobacterium tuberculosis Chaperonin 10 Heptamers Self-Associate through Their Biologically Active Loops - Roberts, Michael M. (American Society for Microbiology, 2003)
The crystal structure of Mycobacterium tuberculosis chaperonin 10 (cpn10(Mt)) has been determined to a resolution of 2.8 Å. Two dome-shaped cpn10(Mt) heptamers complex through loops at their bases to form a tetradecamer with 72 symmetry and a spherical cage-like structure. The hollow interior enclosed by the tetradecamer is lined with hydrophilic residues and has dimensions of 30 Å perpendicular to and 60 Å along the sevenfold axis. Tetradecameric cpn10(Mt) has also been observed in solution by dynamic light scattering. Through its base loop sequence cpn10(Mt) is known to be the agent in the bacterium responsible for bone resorption and for the contribution towards its strong T-cell immunogenicity. Superimposition of the cpn10(Mt) sequences 26 to 32 and 66 to 72 and E. coli GroES 25 to 31 associated with bone resorption activity shows them to have similar conformations and structural features, suggesting that there may be a common receptor for the bone resorption sequences. The base loops of cpn10s in general also attach to the corresponding chaperonin 60 (cpn60) to enclose unfolded protein and to facilitate its correct folding in vivo. Electron density corresponding to a partially disordered protein subunit appears encapsulated within the interior dome cavity of each heptamer. This suggests that the binding of substrates to cpn10 is possible in the absence of cpn60.